Protection for Workers in The Fire Service Palembang City - Ahmad Yani Kosali; Dita Marisa Putri; Syaiful Sahri (Dwijendra University, 2021)
In the implementation of national development, the workforce has a very important role and position as actors and development goals and is required to participate and play an active role with entrepreneurs in efforts to improve and improve the nation's standard of living by increasing production and work productivity. Peace of mind and tranquility of workers can only be achieved if employers and workers can understand and live up to their respective rights and obligations so as to foster mutual understanding, mutual respect, and respect without neglecting the values ​​of rationality and accountability. The development of the manpower sector as part of efforts to develop human resources is an integral part of national development as the practice of Pancasila, and the implementation of the 1945 Constitution, is directed at increasing human dignity, dignity and capabilities, as well as confidence in oneself in in order to create a prosperous, just and prosperous society both materially and spiritually.